Recent developments of proton exchange membranes for PEMFC: A review - Parekh, Abhi (Frontiers in Energy Research, 2022)
The decreasing abundance of conventional energy resources of nature, such as crude oil, natural gas, coal, and so on is putting forward the issues of energy shortcoming for the future. With a sentiment of this, most researchers are now directing either on non-conventional resources that already prevail or invent it. The most promising non-conventional energy resource is the hydrogen energy which can be used in fuel cell to get electricity. Therefore, a number of researchers are putting a light on developing the most efficient and affordable fuel cell. This review is mainly focused on the developments of proton exchange membranes (PEMs) in two parts as low and high temperature PEMs for proton exchange membrane fuel cell (PEMFC) and based on that some outperformed PEMs are mentioned in the respective tables. Most of the energy and automobile industries are concentrating to apply PEMFCs for power generation and to apply in vehicles. The cost of PEMFCs is higher due to manufacturing cost of PEM. Therefore, researches in PEMs are now in trend to reduce the cost, to improve efficiency, and to withstand particular operating conditions. In this review paper, recent developments in PEM by number of researchers and the importance of it in near future have been elicited.